Mitigasi Risiko Sistem Informasi Perpustakaan Perguruan Tinggi Swasta XYZ Menggunakan Management of Risk (MOR) - Yulhendri Yulhendri; Setianingsih; Hannah Patricia; Syifa Maulida Akmalia; Arif Apriansah; Ariansah (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
of the libraries in XYZ private university provides an information system to support library services such as borrowing books, extending the loan period, and returning books. This information system is inseparable from the risks and impacts that threaten its use. The purpose of this research is to analyze the risks contained in the information system using the ITIL framework. The ITIL framework is used as a guide in developing operational steps so that the continuity of library information system services can run well. Based on the research that has been done, the results show that there are 5 risks consisting of 2 risks with low risk levels, 1 risk with medium risk levels, and 2 risks with high risk levels